2016
DOI: 10.1007/s12291-016-0572-y
|View full text |Cite
|
Sign up to set email alerts
|

Filarial Abundant Larval Transcript Protein ALT-2: An Immunomodulatory Therapeutic Agent for Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) that accounts for about 5-10 % of all diabetes cases results from the autoimmune destruction of the insulin-producing beta cells in the pancreas. It is characterized by severe inflammatory reaction mediated by pronounced T helper type-1 response. Parasitic infections having the ability to skew the host immune responses towards type-2 type as a part of their defense mechanism are able to induce protection against autoimmune diseases like T1D. Hence, the present study is undertaken to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In our earlier study (Reddy et al ., 2016) r Bm ALT-2 was found to be more effective in ameliorating T1D. By the end of the fifth week after initiating treatment, all the diabetic mice had turned to normal.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our earlier study (Reddy et al ., 2016) r Bm ALT-2 was found to be more effective in ameliorating T1D. By the end of the fifth week after initiating treatment, all the diabetic mice had turned to normal.…”
Section: Discussionmentioning
confidence: 95%
“…(2010) have shown that the T-cell epitopes of ALT2 from the filarial parasite Brugia malayi induce high levels of IL-10 secretions along with suppression of IFN-γ and IL-12 cytokines, suggesting their possible involvement in the modulation of the host immune system. In the earlier study from our laboratory, recombinant B. malayi abundant larval transcript 2 (r Bm ALT-2) with its effective immunomodulatory activity was shown to be a promising alternative therapeutic agent for T1D (Reddy et al ., 2016). Hence, in the present study, we have assessed and compared the curative effects of r Wb L2 and r Bm ALT-2 by administrating them individually and in combination to treat STZ-induced T1D in mice.…”
Section: Introductionmentioning
confidence: 99%
“…malayi endemic area [ 44 ]. Recombinant BmALT-1 and BmALT-2 have been evaluated as vaccine candidates [ 43 , 45 , 46 ], and the BmALT-2 immunomodulatory activity has been assessed as a prophylactic tool against diabetes induced by streptozotocin in mice [ 47 ].…”
Section: Recombinant Antigensmentioning
confidence: 99%
“…In total, 29 studies compared baseline measures of diabetes or pancreatic inflammation in those with and without helminth infection. Seventeen studies (59%; 11 animal, 6 human) reported lower measures of diabetes or pancreatic inflammation [14,25,32,68,[72][73][74][75][76][77][78][79][80][81][82][83][84], 6 (21%; all human) demonstrated higher measures of these factors [6,[85][86][87][88][89], and 5 (17%; all human) showed no association with respect to helminth infections [53,58,59,71,90]. In the final study there was no difference in hemoglobin A1c or fasting glucose regardless of helminth infection or antiretroviral status among HIV-infected individuals, while among HIV-uninfected individuals, soil-transmitted helminth (STH) infection was inversely associated with hemoglobin A1c (5.2% vs. 5.5% in STH-uninfected controls) after adjustment for age and sex [69].…”
Section: Helminths and Diabetesmentioning
confidence: 99%
“…In comparison to the 6 human studies, 11 animal studies with mouse models using Schistosoma species (n = 7), Fasciola hepatica (n = 2), and filarial species (n = 2) also documented lower measures of diabetes or pancreatic inflammation among helminth-infected animals [72,[75][76][77][78][79][80][81][82][83][84]. Seven of 11 documented histopathological changes of the pancreas in mice and found that helminth infection was associated with less pancreatic inflammation, degradation, and other architectural changes in mice who were infected or exposed to helminth antigens as compared to uninfected mice [72,[76][77][78][79][80][81]. These studies also documented a lower incidence of diabetes between infected and uninfected mice, and via correlations with pancreatic histopathological changes suggested helminths may possibly protect against autoimmune diabetes.…”
Section: Helminths and Diabetesmentioning
confidence: 99%